Analytical presentation of symmetrized vibrational functions of high symmetry molecules for applications in molecular spectroscopy and chemical physics: Accurate prediction of the vibrational spectrum of GeH4 up to 8000 cm−1 as a relevant application example; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 321 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Fomchenko A. L. Anna Leonidovna; Bauerekker Z. Kh. Zigurd Khermann (2024, 2024)
Title screen